Bigger Is Not Always Better: Tumor Size and Prognosis in Advanced Melanoma - Warner, Allison Betof; Postow, Michael A. (Clinical cancer research, 2018)
Tumor burden is a key consideration for the treatment of solid malignancies. Large baseline tumor size (an assessment of volume of disease in target lesions prior to treatment), elevated lactate dehydrogenase (LDH), and site of disease are prognostic of poor overall survival (OS) for patients with advanced melanoma treated with pembrolizumab. Clin Cancer Res; 24(20); 4915–7. ©2018 AACR. See related article by Joseph et al., p. 4960